Identidad corporativa para el posicionamiento del hostal “mi casita” en la parroquia de Balsapamba, cantón San Miguel año 2019 - Verdesoto Camacho, Rolando Sebastian (2019)
The corporate image of a company is very important in the market because it lacks a differentiating and lasting value in the mind of the consumer, for this reason the development of this research project responds to the need and design in the image of the hostel, which is affected by the proliferation of designs. The hostel "Mi Casita", is characterized for being the pioneer in the parish of Balsapamba in offering products and services of lodging and gastronomy, with 10 years of experience and solidity in the Balsapambeño market, it was determined the need to establish a solid image that help the effective strengthening of the company and thus better position in the mind of the consumer. The objectives pursued when building a solid image is: improve the visualization of the brand, differentiate from the competition, create a sense of belonging by the employees of the company and the client, ensure that the service provided is optimal and mainly generate a favorable public opinion for the company. Keywords: corporate image, solid brand, market research, brand manual, strategies, positioning